Long‐term outcome of patients receiving haematopoietic allogeneic stem cell transplantation as first transplant for high‐risk Hodgkin lymphoma: a retrospective analysis from the Lymphoma Working Party‐EBMT. (8th November 2021) - Gutiérrez‐García, G.; Martínez, C.; Boumendil, A.; Finel, H.; Malladi, R.; Afanasyev, B.; Tsoulkani, A.; Wilson, K. M. O.; Bloor, A.; Nikoloudis, M.; Richardson, D.; López‐Corral, L.; et al.
Summary: We analysed long‐term outcome of patients receiving haematopoietic allogeneic stem cell transplantation (allo‐HSCT) as a first transplant for high‐risk Hodgkin lymphoma (HL). One hundred and ninety patients were included in this study, 63% of them had previously received brentuximab vedotin and/or checkpoint inhibitors. Seventy patients (37%) received an unrelated donor allo‐HSCT, 99 (51%) had myeloablative conditioning (MAC) and 60% had in vivo T‐cell/depleted grafts (TCD). The 100‐day cumulative incidence (CI) of grade II‐IV acute graft‐versus‐host disease (GVHD) was 25% and the 3‐year CI of chronic GVHD was 38%. The 3‐year CI of non‐relapse mortality (NRM) and relapse rate were 21% and 38% respectively. After a median follow‐up of 58 months, 3‐year overall survival (OS) and progression‐free survival (PFS) were 58% and 41% respectively. Multivariate analysis showed that, in comparison to reduced‐intensity conditioning regimens with or without TCD, MAC using TCD had similar NRM and a lower risk of relapse leading to significantly better OS and PFS. MAC without TCD was associated with higher NRM and worse survival outcomes. These results suggest that in patients with high‐risk HL and candidates of allo‐HSCT, a MAC strategy with TCD might be the best option.